N (6)-methyladenosine modification and METTL3 modulate enterovirus 71 replication - Hao, Haojie (Nucleic Acids Res, 2019)
N (6)-methyladenosine (m(6)A) constitutes one of the most abundant internal RNA modifications and is critical for RNA metabolism and function. It has been previously reported that viral RNA contains internal m(6)A modifications; however, only recently the function of m(6)A modification in viral RNAs has been elucidated during infections of HIV, hepatitis C virus and Zika virus. In the present study, we found that enterovirus 71 (EV71) RNA undergoes m(6)A modification during viral infection, which alters the expression and localization of the methyltransferase and demethylase of m(6)A, and its binding proteins. Moreover, knockdown of m(6)A methyltransferase resulted in decreased EV71 replication, whereas knockdown of the demethylase had the opposite effect. Further study showed that the m(6)A binding proteins also participate in the regulation of viral replication. In particular, two m(6)A modification sites were identified in the viral genome, of which mutations resulted in decreased virus replication, suggesting that m(6)A modification plays an important role in EV71 replication. Notably, we found that METTL3 interacted with viral RNA-dependent RNA polymerase 3D and induced enhanced sumoylation and ubiquitination of the 3D polymerase that boosted viral replication. Taken together, our findings demonstrated that the host m(6)A modification complex interacts with viral proteins to modulate EV71 replication.